2010
DOI: 10.3109/10641961003686450
|View full text |Cite
|
Sign up to set email alerts
|

Doubling of Water Intake Increases Daytime Blood Pressure and Reduces Vertigo in Healthy Subjects

Abstract: We studied the effect of increased water intake on ambulatory BP in healthy individuals. BP was recorded after two weeks of either regular (RWI) or extra water intake (EWI, an additional 30 ml water/kg body weight per day) in 20 healthy subjects (10 males, 10 females).The extra water intake (RWI: 1.7 ± 0.59 l, EWI: 3.7 ± 0.84 l, respectively, p< 0.0001, i.e. an increase of 2 litres) induced an increase in mean arterial daytime BP from 89.0 ± 5.5 mmHg during RWI to 91.4 ± 6.4 mmHg during the EWI phase (p= 0.005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
2
0
4
Order By: Relevance
“…A systematic review demonstrated that water intake was associated with reduced energy intake and therefore obesity prevention [5]. Some clinical trials showed no significant effect of water consumption on body weight [24][25][26]; however, in a clinical trial, consumption of 500 mL water before meals led to a greater weight loss compared to a hypocaloric diet in middle-aged and older adults [6]. It must be kept in mind that findings from clinical trials cannot be generalized to the routine life because these interventions are conducted in short time with high doses.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated that water intake was associated with reduced energy intake and therefore obesity prevention [5]. Some clinical trials showed no significant effect of water consumption on body weight [24][25][26]; however, in a clinical trial, consumption of 500 mL water before meals led to a greater weight loss compared to a hypocaloric diet in middle-aged and older adults [6]. It must be kept in mind that findings from clinical trials cannot be generalized to the routine life because these interventions are conducted in short time with high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Water intake can acutely reduce heart rate and increase blood pressure in normotensive individuals, and this effect can last for up to 60 min [5,36]. Furthermore, Jormeus reported that the changes in blood pressure were the consequences of the amount of water per se, and not due to the potential confounders such as changes in salt intake [37]. Therefore, the increase in blood pressure in the isotonic beverage group was likely due to the better water retention and hydration status instead of the salt intake, and the slight changes in heart rate are to balance the effect of normal fluctuations in blood volume on blood pressure [5].…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados ratificam a premissa que a IA influencia as atividades hemodinâmicas e autonômicas cardiovasculares, alterando a resistência vascular periférica, pressão arterial, frequência cardíaca e atividade vagal cardíaca 14,16,22,25,[30][31][32][33][34] .…”
Section: Discussionunclassified